El ecomarxismo entre el Antropoceno y el Capitaloceno: rupturas metabólicas, capital fósil y régimen ecológico - Álvaro Andrés Villegas (Universidad de los Andes, 2021)
Objective/Context: The article focuses on the discussions on the Anthropocene and Capitalocene in eco-marxism, especially in the Metabolic Rift and World-Ecology schools. These entered into a conceptual confrontation on how this new state of the Earth System should be named, its characteristics, agents, genesis and relationship with capitalism. Methodology: A critical reading of the recent bibliography on the concepts of Anthropocene and Capitalocene is made, especially that produced by eco-marxism. Conclusions: The main differences between the aforementioned schools are related to the beginning of the Anthropocene and the Capitalocene, which for the first would refer to the beginning of capitalism, while for the second it would refer to the Industrial Revolution, or the Great Acceleration; the relevance of the nature-society dichotomy has also been debated. It is also possible to identify several fundamental agreements on the central role of capital accumulation, the responsibility of capitalists in the process of global change, and the systemic character of the contemporary crisis of capitalism. Originality: The article makes a systematic review of one of the most important discussions of eco-marxism, a field of great relevance within Marxist theory at present. Although a few analogous reflections have been published, these are biased due to their ascription to one of the two competing schools.